Hematopoietic Reaction of Broiler Birds Fed Graded Levels of Boiled Baobab (Adansonia digitata) Seed Meal as a Replacement for Soyabean in the Humid Tropics - Saulawa, L.A.; Yahaya, M.A.; Ukpabi, U.H. (Pakistan Journal of Nutrition, 2015)
A study was carried out at the research farm of faculty of agriculture, Abia State University Uturu, in order to determine the hematopoietic reaction of broiler birds fed graded levels of boiled baobab seed meal as a replacement for soya beans meal. Three hundred (300) day old chicks of Anak breed were randomly allocated to five (5) treatments groups of A, B, C, D and E with 60 birds per treatment group replicated thrice of twenty (20) birds per replicate in a Complete Randomized Design (CRD). Treatment group A served as a control group fed diet free (0%) of the boiled baobab seed meal while treated groups B, C, D and E diets were replaced at 25, 50, 75 and 100% levels of baobab seed meal in place of soya beans meal. Treated diets and water were supplied ad-libitum and all management practices strictly adhered to. Blood samples were randomly collected from three (3) birds per replicate at the termination of the study at 8th weeks, after which the blood was sent immediately to the University Laboratory for analysis. Results of the findings revealed insignificant differences (p>0.05) in the mean values of PCV amongst all the treated groups (Table 2). On the other hand significant differences (p<0.05) due to treatment effects (Table 2) were observed in the mean values of Hb, RBC, WBC, MCV, MCHC, MCH, LYMPH, BASO and NEUTRO amongst the treated groups with treatments group A and B having greater mean values which were statistically different from treated groups C, D and E. However, the results of these findings were within the normal range reported by some authors signifying that the treated birds were healthy and the boiled test ingredient can be used to replace soya bean meal to the maximum level of 100% without any adverse effects in the hematological indices of the birds.